Development and Initial Validation of the Humor Climate in Sport Scale - Schei, Gaute S.; Haugen, Tommy; Stenling, Andreas; Grøtting, Anniken; Peters, Derek M.; Høigaard, Rune (Frontiers in Psychology, 2021)
In sport teams, humor is an essential element that influences communication processes, and plays an important role in group dynamics. Despite this, no current instrument is presented in the literature to measure humor climate in sport teams. Therefore, the current study presents the development and initial validation of the Humor Climate in Sport Scale (HCSS). The aim was to assess content, structural and concurrent validity of the developed instrument, and to examine differential item functioning (DIF) as a function of sex. Three different phases were completed in this study. The first phase involved focus groups (n = 5) that explored humor as communication in a team sport context. In phase 2, information from the focus groups was used to create a pool of potential items for the questionnaire. Two discussion groups with sport science students contributed to the development of 80 potential items, that two different expert groups then assessed for item quality. The final version of the instrument after this phase contained 14 items, representing three different humor dimensions. In phase 3, two independent samples with a total number of 776 participants were recruited for the psychometric evaluation of the instrument. EFA, ICM-CFA, and ESEM analysis were performed, supporting a three-factor structure with positive humor, negative humor in-group, and negative humor out-group. In addition, partial DIF as a function of sex on the negative humor dimensions was found, indicating differences in how male and female interpret the negative humor items. The findings in the current study expand our understanding of humor in sport teams and may be a starting point for further research on humor climate in sport teams and its role in group function.